HARVEST DATES ESTIMATION FOR ‘NIAGARA ROSADA’ GRAPEVINE AT THE “PÓLO TURÍSTICO DO CIRCUITO DAS FRUTAS” REGION, SÃO PAULO STATE, BRAZIL - BARDIN, Ludmila; JÚNIOR, Mário José PEDRO; MORAES, Jener Fernando Leite de; PEDRO, Fábio Giardini (Scientia Agraria, 2009)
The São Paulo State region known as “Pólo Turístico do Circuito das Frutas” congregates producing ‘Niagara Rosada’ grapevine counties, being responsible for 60% of the state production. For the economical and rational exploitation of that agricultural activity it is necessary to apply the technological advances, mainly on its qualitative and quantitative aspects. Once the previous knowledge of the harvest dates allows the planning of viticultural activities by the producers. Mean monthy maximum and minimum air temperatures were used to acquire the number of days needed for the grapevine to complete growing seasons (pruning to harvest), based on growing degree-days (1549 GDD). Therefore it was possible to elaborate maps for the different probable harvest dates in the “Pólo Turístico do Circuito das Frutas” region considering different pruning dates. The ‘Niagara Rosada’ harvest dates for different pruning dates varied from November 30th to February 25th when comparing the west and east side of the study area.